Digital-Based Learning Application Model in Schools - Wardoyo, Munadjat; Sumaryana, Asep; Komalasari, Kokom; Bestari, Prayoga (International Journal of Supply Chain Management, 2021)
The rapid development of science and technology has been anticipated by the government through the Merdeka Belajar (freedom to learn) policy initiated by the Education and Culture Ministry of the Republic of Indonesia. One of the responses about that policy was the development of a digital-based learning application model. This study used a research design based on Resarch and Development (R D). The purposes of this study is to develop a digital-based learning model that is able to provide freedom of learning for teachers and students in the digital learning process. The results showed that the digital-based learning model which its development was based on inputs in the form of an independent learning policy and the digitalization movement; element of process in the form of student-centered learning; element of output in the form of fun and flexible learning; and the element of intact results in the form of the establishment of student competencies.